2021
DOI: 10.1371/journal.pone.0249489
|View full text |Cite
|
Sign up to set email alerts
|

A mindfulness-based, stress and coping model of craving in methamphetamine users

Abstract: There is increasing interest in the role of mindfulness and mindfulness-based interventions to optimize recovery from a substance use disorder (SUD). However, relatively little is known about the theory-based psychological and social pathways whereby mindfulness could have beneficial effects for managing a chronic, relapsing SUD. Informed by Revised Stress and Coping Theory, the present cross-sectional study examined affective, cognitive, and social pathways whereby mindfulness is associated with lower methamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…The results indicated that MBRP helped mitigate drug cravings in TC visitors. This is consistent with the findings of previous studies (17,20). In explaining the findings of the current research, it can be said that the purpose of MBRP is to create awareness and accept thoughts, emotions and feelings through practicing mindfulness and using mindfulness skills as a coping strategy in facing high-risk situations (29).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results indicated that MBRP helped mitigate drug cravings in TC visitors. This is consistent with the findings of previous studies (17,20). In explaining the findings of the current research, it can be said that the purpose of MBRP is to create awareness and accept thoughts, emotions and feelings through practicing mindfulness and using mindfulness skills as a coping strategy in facing high-risk situations (29).…”
Section: Discussionsupporting
confidence: 92%
“…Recurring encounters with present experiences, maintaining awareness, and accepting and tolerating craving-induced distress can lead to habituation of distress and disrupt negative reinforcement cycles of substance abuse in response to drug cravings (20). Therefore, substance abuse therapies that promote normal interoceptive awareness could target flexibility and focus on the separation of drug craving from substance abuse (21).…”
Section: Introductionmentioning
confidence: 99%
“…Tests of this hypothesis have been promising [49,50]. Mindfulness can serve as an effective buffer against stressors both proximal, such as coping with substance use cravings [51] or mental fatigue from multitasking [52], and distal, by reducing perceptions of and reactions to stress over time [48]. Short-term MIIs with parents have been shown to increase levels of mindfulness and subjective wellbeing, decrease levels of parenting stress, and improve youth outcomes, such as externalizing behaviors [5,7,53].…”
Section: Stress Parenting and Mindfulnessmentioning
confidence: 99%
“…Noticeably, mindfulness seemed to attenuate substance craving through a moderating effect on negative affect (7,8). Recently, Mallik et al's, from a sample of patients who completed treatment for substance use disorders, suggested that both mindfulness and psychological flexibility contributed to variance in substance craving, while controlling for severity dependence (9).…”
Section: Introductionmentioning
confidence: 99%